The Granular Origins of Macroeconomic Fluctuations in Europe - Ebeke, Christian (IMF Working Papers; Working Paper ;, 2017)
This paper investigates the microeconomic origins of aggregate economic fluctuations in Europe. It examines the relevance of idiosyncratic shocks at the top 100 large firms (the granular shocks) in explaining aggregate macroeconomic fluctuations. The paper also assesses the strength of spillovers from large firms onto SMEs. Using firm-level data covering over 14 million firms and eight european countries (Austria, Belgium, Finland, France, Germany, Italy, Portugal and Spain), we find that: (i) 40 percent of the variance in GDP in the sample can be explained by idiosyncratic shocks at large firms; (ii) positive granular shocks at large firms spill over to domestic SMEs' output, especially if SMEs' balance sheets are healthy and if SMEs belong to the services and manufacturing sectors.